2020
DOI: 10.9778/cmajo.20190204
|View full text |Cite
|
Sign up to set email alerts
|

Association between media attention and presentation of vaccination information on Canadian chiropractors’ websites: a prospective mixed-methods cohort study

Abstract: Background: Historically, some chiropractors have been critical of vaccination, and this has been the subject of recent media attention in Canada. We explored the association between media attention and public dissemination of vaccination information on Canadian chiropractors' websites. Methods: In 2016, we identified all Canadian chiropractors' websites that provided information on vaccination by extracting details from the regulatory college website for each province using the search engine on their "find a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Sharing research with the news media is an effective way to close this gap and reach audiences that can translate findings into action [5]. Indeed, a diverse body of research suggests media coverage of health research influences policy [6,7], medical practice [8][9][10][11], and consumer behavior [12][13][14][15][16][17]. Some studies have found direct correlations between media reporting and public health outcomes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Sharing research with the news media is an effective way to close this gap and reach audiences that can translate findings into action [5]. Indeed, a diverse body of research suggests media coverage of health research influences policy [6,7], medical practice [8][9][10][11], and consumer behavior [12][13][14][15][16][17]. Some studies have found direct correlations between media reporting and public health outcomes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%